Matrizes tridimensionais como agentes para capeamento pulpar direto - Cunha, Diana Araújo (2023)
Direct pulp capping aims to preserve the vitality of the tooth, encouraging the pulp to form reparative dentin at the site of exposure. This tissue reaction happens through the beneficial effects of a bioactive material applied to the lesion. This thesis is completed by two chapters that aim to investigate the behavior of three-dimensional matrices (TM) associated with biomaterials. Chapter 1 is a literature review with the objective of exploring the use of MT associated with bioactive materials as a pulp capping agent, being used under pulp exposure in an animal model. For this, a search was performed in the PubMed database (Medline) from 2012 to 2022, listing the terms “Demineralized Dentin Matrix”, “Dental Pulp Capping”, “Scaffold” and “Hydrogel”. 81 articles were found and soon after excluding laboratory studies, reviews, case reports and randomized clinical studies, in the end, 12 were selected. How MT was used in the studies were of organic, synthetic and hybrid composition. The bioactive materials ranged from drugs, lipid mediators, stem cells, monomers, growth factor concentrates and dentin matrix proteins. The main methods used to analyze the regenerative effects were through histological, radiographic and immunohistochemical analysis. This review exhibited that MT of natural composition associated with bioactive molecules showed more promising results than the commercial controls used. Chapter 2 deals with in vivo research with the objective of developing and evaluating the effectiveness of a three-dimensionally (3D) printed microgel supplemented with dentin matrix molecules (MMD). Pulp exposures were performed on the first upper molars of Wistar rats and treated, following the division of groups: (1) inert material - negative control, (2) microgels, (3) microgels + MMD 500 μg/ml, (4) microgels + MMD 1000 μg/ml, (5) microgels + platelet-derived growth factor (PDGF 10 ng/ml) or (6) MTA (n = 14/group). After 4 weeks, the animals were euthanized, and histological evaluation was performed. All samples from the microgel + 500 μg/ml, microgel + 1000 μg/ml, microgel + PDGF and MTA groups showed the formation of organized pulp tissue and tertiary dentin. Dentin bridge formation was the most and pulp necrosis was less evident in the microgel + MMD groups compared to the MTA. Thus, it can be concluded that 3D-printed light-curing microgels incorporated with MMD exhibited favorable inflammatory cell response, and significantly more tertiary dentin deposition, being a promising biomaterial.